IMPACT OF AUDIT QUALITY ON EARNINGS MANAGEMENT OF LISTED MANUFACTURING COMPANIES IN NIGERIA - Sanni, Mubaraq; Mustapha, Abdulrasaq; Victoria Adekanye, Adeoluwa (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
News on the collapse of business organization in Nigeria and by extension across globe particularly in the western economies that ought to have gotten to the awareness of the stakeholders are usually cover up or distorted through the manipulation of accounting figures. External auditors that are expected to discover various accounting manipulation also seems not be effective. This scenario motivates this study to investigate the effect of audit quality on earnings management of listed manufacturing companies in Nigeria. This study was achieved by examining the effect of audit firm size, joint audit service and auditor’s experience on earnings management of the listed manufacturing company in Nigeria. Ex-post facto research design was employed with the population consisting of seventy-six (76) listed manufacturing companies, and sixty-four (64) out of the companies were chosen as the sample size using Krejcie and Morgan (1970) sample size determination table and fifty-five (55) was used due to the availability of data. Descriptive and inferential statistics (random effect regression analysis with OLS techniques) were employed in the analysis of the secondary data collected from the annual reports and accounts of the chosen sample companies for the period of five years (2013-2017). The study found out that audit firm size and joint audit service has a significant negative effect on the level of earnings management practice of listed manufacturing companies in Nigeria at 5% significant level (t-value of -0.3238 and -1.1757 with p-value of 0.002 and 0.000 respectively). This audit firm size and joint audit restrict and reduce the level of earnings management in listed manufacturing companies. However, auditor experience has no significant relationship with earnings management (t-value of -0.0021 with p-value 0.063). The study thereby concluded that audit firm size and joint audit service has a significant negative impact with earnings management practice of listed manufacturing companies in Nigeria, while auditor’s experience has no significant effect. Therefore, the study recommends that management should make use of large audit firms to audit their financial statement and the audit firms should emphasize more on high professional standards.